Model Pengembangan Kelembagaan Kecamatan Yang Berbasis Pada Kompleksitas Dan Prioritas Layanan Publik (Studi Kasus Di Kecamatan Lubuk Basung Dan Ampek Angkek Kabupaten Agam, Sumatera Barat) - Andari, Rosita Novi (Pusat Pembelajaran dan Strategi Kebijakan Talenta Aparatur Sipil Negara Nasional, 2010)
Institutional Development District is very urgent to improve the quality of district services as the spearhead of the public service. Institutional development district model consists of four aspects: (1) tasks and functions, (2) organizational structure, (3) governance (management districts), and (4) personnel and infrastructure resources, which is formulated based on the complexity and public service priorities held districts. The results showed that the application formulation of institutional development model district in Lubuk Basung and Ampek Angkek shows similar results for mass organizations that include tasks and functions and organizational structure with four sub sections. The model of governance (management district) and personnel and infrastructure resources tend to be different, where one-door mechanism and integrated services around the district was held in the District of Lubuk Basung, while in District Ampek Angkek with the mechanism of integrated services around the district and services online. The personnel and infrastructure resources support services in the District of Lubuk Basung is not adequate, while in Ampek Angkek.